Synthesis of advanced asbestos-free material using rice husk ash and marble waste for thermal insulation applications - Verma, Sarika; Bajpai, Harsh; Suresh, S.; Mili, Medha; Gupta, Ritesh Kumar; Shetty, Rohit; Kamble, Sanjay; Khan, Mohd. Akram; Hashmi, S. A. R.; Srivastava, A. K. (Biomass Conversion and Biorefinery, 2023)
The importance and utilization of advanced thermal insulating materials increase due to their broad and irreplaceable energy conservation role. This paper describes the novel way of achieving insulating material. In two waste by-products, namely rice husk ash (RHA), agriculture waste, and marble waste powder (MWP), industrial waste has been utilized to make asbestos-free advanced material for thermal insulation. A novel method for making asbestos-free advanced material for thermal insulation using RHA and marble waste's inherent characteristics has developed mechano-chemical for appropriate physico-chemical consolidation, densification, and ceramic processing route. The Si and Ca sources undergo a series of chemical transformations accompanied by mass transfer and thermal reactions during the synthesis process. The formation of this silicate compound occurs due to the presence of higher contents of CaO in marble waste powder (MWP) and silica in rice husk ash (RHA), resulting in thermal insulating characteristics in the advanced thermal insulation material (ATIM). Raman spectra of ATIM after heating at 1100 degrees C were mainly amorphous, which had a broad peak at 1072 cm(-1). This shows thermal transformation occurs after the heating process, the admixture of tailored powder, and fly ash (FA). The density of the ATIM is found to be 1150 kg/m(3). The phase transformation (glass transition temperature) was found in all the samples between 600 and 800 degrees C. The mechanical properties, namely the compressive strength and impact strength evaluation test, showed that the material meets the standard specifications for ceramic tiles. The thermal conductivity (W/mK) was calculated from different temperature 30, 50, 100,150, and 200 degrees C and found to be 0.571, 0.541, 0.516, 0.498, and 0.477, respectively. According to the test results, it is concluded that ATIM from MWP, RHA, and FA were excellent insulating components. The novel feature of the reported process is the development of non-toxic and asbestos-free thermal insulating low-cost material wherein chemically designed and mineralogically formulating desired phases lead to the homogeneous and effective thermal insulating matrix. The process is feasible, simple, cheap, and highly energy-efficient, increases production efficiency, and is environmentally friendly. The widespread use of advanced material for a broad application spectrum ranges from aerospace, automobile, electronics, transportation, construction, to other industries.
Keywords: Asbestos; Fly ash; Marble waste; Material; Rice husk ash; Thermal insulation